PENGARUH PEMBELAJARAN MATA KULIAH KEWIRAUSAHAAN TERHADAP INTENSI KEWIRAUSAHAAN - Umi Choiriyah (Universitas muhammadiyah malang, 2015)
The research purpose of this study is to analyze the influence of entrepreneurship course on entrepreneurial intention. A simple linear regression was use as a statistical tool. The research used 85 of college students as a respondent. The result shows that entrepreneurship course has a positive significant effect on entrepreneurial intention. The recomendation is educational institutions should be facilitate entrepreneurship activities space in campus.